Effect of fatty liver and fibrosis on hepatocellular carcinoma development in patients with chronic hepatitis B who received nucleic acid analog therapy. Issue 4 (24th January 2023) - Keitoku, Taisei; Tamaki, Nobuharu; Kurosaki, Masayuki; Inada, Kento; Kirino, Sakura; Uchihara, Naoki; Suzuki, Keito; Tanaka, Yuki; Miyamoto, Haruka; Ishido, Shun; Yamada, Michiko; Nobusawa, Tsubasa; et al.
Abstract: The number of patients with fatty liver has been increasing worldwide; however, the significance of fatty liver in patients with chronic hepatitis B who are receiving nucleic acid analog (NA) therapy remains unclear. Thus, we aimed to determine whether fatty liver affects the development of hepatocellular carcinoma (HCC) in patients receiving NA therapy. This study included 445 patients who received NA therapy, and the development of HCC was investigated. The primary outcome was the association between fatty liver and HCC development. During a mean follow‐up period of 7.4 years, 46 patients (10.3%) developed HCC. No significant difference in the cumulative incidence of HCC was observed between patients with fatty liver and those without ( p  = 0.17). Multivariable analysis for age, gender, platelet count, alanine aminotransferase level at 1 year following NA therapy, and fatty liver revealed that the presence of fatty liver was not a significant factor for HCC development (hazard ratio [HR]: 0.96, 95% confidence interval [CI]: 0.5–1.9). In another multivariable analysis for advanced fibrosis, gender, and fatty liver, advanced fibrosis was found to be a significant factor for HCC development (HR: 9.50, 95% CI: 5.1–18) but not fatty liver (HR: 0.90, 95% CI: 0.5–1.7). In conclusion, in patients with chronic hepatitis B who received NA therapy, advanced fibrosis was found to be an important risk factor for HCC development but not fatty liver, suggesting the importance of providing treatment before the progression of liver fibrosis regardless of the presence of fatty liver.